Evolutionary diversification of C2 photosynthesis in the grass genus Homolepis (Arthropogoninae) - Alvarenga , Joyce Pereira (2022)
The process of C4 evolution, recognized as a convergent process, emerged smoothly and independently, in a way that novel traits were assembled many times in a variety of species. Besides the decrease in CO2 concentrations, other environmental factors such as increases in temperature, light intensity and water scarcity, contributed to induce the modifications observed in C4 species. Traits that emerged and represented a fitness advantage were then selected. Important anatomical and biochemical modifications occurred along this process, and there are species that maintained both C3 and C4 characteristics. These intermediate species represent the bridge between C3 and C4, and they have a great importance for studies on C4 evolvement. There are a great number of important C4 crops from the grass family. They come to be more productive than C3 species; especially in environments with severe conditions caused by climate change. Noteworthy, the majority of C4 species is found in the grass family, however studies on C4 evolution and particularly with intermediate species are concentrated in eudicots. For this reason, the aim of this work was to identify the characteristics of species from the grass genus Homolepis regarding their photosynthetic types and characterize their bundle sheath cells. For that, anatomical and gas exchange characterization were conducted in four Homolepis species, Homolepis glutinosa, Homolepis isocalycia, Homolepis longispicula, Homolepis aturensis and one C4 species Mesosetum loliiforme, that belongs to a sister group. Both anatomical and physiological results demonstrate clearly a gradient in the photosynthetic types. Besides the C4 M loliiforme, it was found one C3 H. glutinosa, one Proto-Kranz H. isocalycia and two C2 H. aturensis and H. longispicula. For most of the anatomical traits it is observed a positive and strong correlation between them and the CO2 compensation point. As the CO2 compensation point increases, with the exception of veins density, the interveinal distance, the number of M cells between veins, the ratio mesophyll: bundle sheath tissue area and the bundle sheath cell measurements also increase for C3 species. In C4 species the opposite happens with lower values, while intermediate species have midway values. An important result was the values found for bundle sheath cells dimension. The results follow a gradient from C3 to C4, and C3 species has bigger cells dimension than C4 species. However, this trend is the opposite of what is discussed in the literature, hence requiring more studies of this kind. In conclusion, this current study aggregates important information about the Homolepis group, contributing with the literature about intermediate species and in the evolutionary processes of CO2 assimilation in grasses.